Service quality assessment of the Quezon City Public Library from one perspective of its users - Cariaga, Esther C. (2010)
Public libraries are information centers that are free for all. It accommodates everyone in whichever community it is in. It helps the community in continuous education of the people. For these, a public library should provide quality services to its clients. The study aimed to find out if the Quezon City Public Library meets its users' need through SERVQUAL. SERVQUAL is an evaluation instrument that measures the service quality of different institutions such as the library. In order to determine the service quality of an institution, it relates the expectation and perception of service quality with the use of gap analysis. A modified SERVQUAL questionnaire was developed to answer the objectives of the study.